Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Project Based Learning (PjBL) pada Materi Harmoni dalam Ekosistem Topik Memakan dan Dimakan untuk Meningkatkan Hasil Belajar Kognitif Peserta Didik Kelas V Sekolah Dasar - Lili Suryanti; Endang Widi Winarni; Abdul Muktadir (UNIB Press, 2026)
The purpose of this study is to develop a PjBL-based LKPD product on the harmony in the ecosystem topic of eating and being eaten to improve the cognitive learning outcomes of fifth-grade elementary school students. The type of research used is Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation and evaluation. The data used are quantitative and qualitative data. Quantitative data were obtained from the results of validation by material, language, and graphic experts, product trials, and effectiveness tests through pretests and posttests. Qualitative data were obtained from the results of interviews, observations, and questionnaires of teacher and student responses. The results showed that the PjBL-based LKPD developed according to the material, language, and graphic expert validators was declared suitable for use. Teacher and student responses were categorized as very positive regarding the appearance and ease of use of the media. In addition, the results of the effectiveness test showed an increase in students' cognitive learning outcomes with an N-Gain Score of 0.7980 which is included in the effective category. Based on these results, it can be concluded that the PjBL-based LKPD is suitable for use to improve the cognitive learning outcomes of fifth-grade elementary school students.